Therapeutic potential of selenium nanoparticles - K, Deepasree; Venugopal, Subhashree (Frontiers in Nanotechnology, 2022)
ABSTRACT Diseases have always been a disconcerting issue and have changed into being an inevitable member of world’s population. Medical advancements have brought in improved treatments for particular ailments but unfortunately those betterments have resulted in either side effects or turned out futile to a certain extend. The emergence of nanotechnology has considerably benefitted medical experts in disease diagnosis and therapeutics. Currently, an expansive range of nanoparticles are being explored for its effectiveness in therapies and one among them is selenium nanoparticle (SeNP). Nano selenium exhibits significant properties which makes it best suited for this purpose. The article highlights the key role of SeNPs in treating major diseases like cancer, diabetes and microbial infections